A meta-study of qualitative research on the junior-to-senior transition in sport - Drew, K.; Morris, R.; Tod, D.; Eubank, M. (Psychology of Sport and Exercise, 2019)
The last decade has seen an increase in empirical research associated with the junior-to-senior transition in sport. Previous research has, however, been idiosyncratic in its nature, focused on understanding the process from domain specific perspective. The purpose of the current study, therefore, was to provide a systematic review of literature focused on the junior-to-senior transition. Specifically, this study: (a) provides an overview and critique of methodological and theoretical decisions which underpin current junior-to-senior transition literature; (b) systematically reviews, evaluates, and analyses literature on the junior-to-senior transition in sport regarding key factors that are perceived to impact the transition; and (c) provides a synthesis of findings regarding the factors that influence the junior-to-senior transition in sport. A total of 27 studies were included in this meta-study. Meta-method, meta-theory, meta-data analysis, and meta-synthesis analyses were conducted on data. Data highlighted that the main method used to research the junior-to-senior transition is cross-sectional individual interviews, with two theories (Stambulova, 2003; Wylleman & Lavallee, 2004) used as the main underpinning theories for data collection. Analysis identified 59 factors that were perceived to impact the junior-to-senior transition. These 59 factors fell into one of 13 themes, which were then categorized into 4 overarching themes: individual factors, external factors, cultural factors, and intervention strategies. A model of junior-to-senior transition, which synthesizes current knowledge, is proposed as a way to explain the process. The current study identifies gaps in current knowledge, highlights practical implications, and identifies future research directions (e.g., longitudinal designs).